2013
DOI: 10.5578/tt.5334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of pleural fluid and serum procalcitonin levels in the diagnosis of parapneumonic pleural effusion

Abstract: PS/S-PCT levels were found to be highly efficient in excluding PPPE but not sufficiently reliable in the diagnosis of it. However, these findings should be reassessed in a larger group of cases that have not been given any antibiotic/anti-inflammatory treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…In the same study, higher leukocyte counts, fever and CRP values (p<0.05) were detected in the PPE group. [6] In our study, in the PPE group significantly higher leukocyte counts were detected (p<0.001). Although a higher percentage of neutrophils was observed in the PPE group, any statistically significant intergroup difference could not be noted.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the same study, higher leukocyte counts, fever and CRP values (p<0.05) were detected in the PPE group. [6] In our study, in the PPE group significantly higher leukocyte counts were detected (p<0.001). Although a higher percentage of neutrophils was observed in the PPE group, any statistically significant intergroup difference could not be noted.…”
Section: Discussionsupporting
confidence: 50%
“…In similar studies investigating the PPE PCT level, the presence of additional disease was also addressed. In the study conducted by Doğan et al, [6] any significant difference was not reported between the PPE and non-PPE groups concerning the presence of additional diseases. In another study, the presence of comorbid disease was significantly more frequent in the MPE group compared to the PPE group (p<0.001).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a prospective study, Doğan et al compared 33 patients with parapneumonic effusions (including 22 empyemas) with controls (nonparapneumonic effusions). Using a cut-off level of 0.105 ng/mL, the sensitivity and specificity of PCT were 67% and 97%, respectively [9]. This case and the evidence from these studies demonstrate that PCT may remain low in localized or contained pulmonary infection, even when clinically and radiologically advanced.…”
Section: Discussion and Literature Reviewmentioning
confidence: 98%
“…18 Estudios más recientes han explorado valores de PCT para identificar causas infecciosas del derrame pleural (DP). 19 Entre las limitantes de los estudios se encuentra la falta de análisis en suero, reproducibilidad de los hallazgos y la variación del rendimiento diagnóstico entre poblaciones. Por tal motivo, el objetivo principal del presente estudio es analizar el comportamiento de PCT sérica al ser evaluada de forma sistematizada en un grupo de pacientes mexicanos confirmados con DPN.…”
Section: Introductionunclassified